Mucuna pruriens seed repeals the hypothalamic-pituitary-testicular axis disruption following carbamazepine treatment in male Wistar rats (Nigerian Journal of Physiological Sciences, 2023)
This study examined the potential effects of Mucuna pruriens (MP) seed powder on the disruptions of the hypothalamic-pituitary-testicular axis caused by the carbamazepine (CBZ) treatment in male Wistar rats. A total of 35 male Wistar rats were randomized into 5 groups (n=7). The animal in group 1 received normal saline (0.2 ml) orally, while groups 2-5 received carbamazepine (CBZ) 25 mg/kg per oral. Groups 1, and 2 were fed with standard rats’ chow, while groups 3-5 rats were supplied with a diet containing MP seed powder at 2.25 g, 1.5 g, and 0.75 g respectively. The serum level of male reproductive hormones, estradiol, seminal profiles, and histoarchitecture of the hypothalamus, pituitary, and testis was delineated. Descriptive and inferential statistics were used to analyze the result. There was a marked decrease in the testicular weight, follicle-stimulating hormone, testosterone concentration, and normal sperm cells in the CBZ, and CBZ + MP (2.25 mg/kg) treatment groups.  There was a marked increase in the testicular tissue lipid peroxidation in the CBZ, and CBZ + MP (g) treated rats in addition to various morphological alterations in the hypothalamus, pituitary, and testis. These anomalies were receded in the CBZ + MP (1.5 g), and CBZ + MP (0.75 g) treatment groups. Consumption of MP (1.5 g, and 0.75 g) may alleviate the injurious effects of CBZ treatment on the hypothalamic-pituitary-testicular functions.